(untitled) (Ágora Journal, 2020)
The year 1837 in Pernambuco marks the rise of Francisco do Rego Barros (Barão da Boa Vista) to power and with him his political project to modernize the province via urban improvements. At that time, historiography highlights that several works were designed or budgeted mainly in the capital and several foreign workers were hired. However, the Baron’s proposal to reformulate the Repartição de Obras Públicas (ROP) was not well accepted by all, subsequently serving as ammunition for opponents and significantly impacting the subsequent elections and insurrectionary movements. In this sense, the present article aims to analyze some of the political clashes between conservatives, governists and beach liberals around the ROP of the Province of Pernambuco present in Diário de Pernambuco and Diário Novo.